Educación y desarrollo rural - Mora Alfaro, Jorge (2001)
The changes experienced by the contemporary society have a particular manifestation in the rural areas of our countries. In is in these social spaces where the most relevant impact of the accelerated economic, political and cultural integration takes it toll; it is in the rural communities, where the consequences of the open economic policies adopted by governmental authorities, are best reflected. These social processes aftermath brings about a substantial change in the rural world that contributes to enlarging the existing divide, as far as human development, between urban and rural areas. In Costa Rica, the redefinition of its development strategy started in the 1980´s. Two decades later, without a clearly defined vision and a growing uncertainty about the future on part of the population, it is an unfinished process. The national economy structural adjustment began in the 1980’s. Currently, there are opposing technical opinions as to its results. In this analysis, it is important to emphasize the impacts of the economic policies implemented in the 1980-2000 period, and the changes in the agrarian structure and social relations originated with the modernization processes experienced by the Costa Rican society as of the 1950´s decade.